Oral administration of leaf extracts of Momordica charantia affect reproductive hormones of adult female Wistar rats - Osonuga Odusoga Adewale; Osonuga Ifabunmi Oduyemi; Osonuga Ayokunle (Asian Pacific Journal of Tropical Biomedicine, 2014)
Objective: To determine the effect of graded doses of aqueous leaf extracts of Momordica charantia on fertility hormones of female albino rats. Methods: Twenty adult, healthy, female Wistar rats were divided into four groups: low dose (LD), moderate dose (MD) and high dose (HD) groups which received 12.5 g, 25.0 g, 50.0 g of the leaf extract respectively and control group that was given with water ad libatum. Result: Estrogen levels reduced by 6.40 nmol/L, 10.80 nmol/L and 28.00 nmol/L in the LD, MD and HD groups respectively while plasma progesterone of rats in the LD, MD and HD groups reduced by 24.20 nmol/L, 40.8 nmol/L and 59.20 nmol/L respectively. Conclusion: Our study has shown that the antifertility effect of Momordica charantia is achieved in a dose dependent manner. Hence, cautious use of such medication should be advocated especially when managing couples for infertility.